The farmer?s view - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Mama Ndelifose Nanyaro explains how growing and eating indigenous African vegetables, such as okra, eggplant, cowpeas and pumpkins, has made her life better. She looks and feels young and strong, despite being 60 years old, and she is proud that she can afford to pay school and hospital fees when she needs to.